EKSPLORASI BAHAN ALAM CILACAP UNTUK PRODUK KESEHATAN PADA KEGIATAN KARYA ILMIAH REMAJA - Prastowo, Muhammad Yogie; Famuji, Tri Stiyo; Fauzi, Yuhansyah Nur; Utami, Tri Fitri Yana; Pertiwi, Yuniariana; Wardani, Tri Kusuma (LPPM Universitas Flores, 2025)
This community service activity focused on conducting an exploration of local natural materials from Cilacap for health products within the Student Scientific Group (KIR) at SMP Negeri 5 Cilacap. The activity aimed to enhance students' understanding and scientific skills regarding the potential of their local biodiversity through a contextual learning approach. The implementation method consisted of three main stages: (1) Delivery of core material on the identification and utilization of natural materials, (2) Independent exploration and discussion by students to observe material samples, and (3) Understanding evaluation through interactive quizzes and reflection. The results demonstrated high enthusiasm and active engagement from the participants. Students were not only able to identify various natural materials and their potential benefits but also showed improved observation and collaboration skills. This activity successfully raised awareness of the value of local wisdom and opened insights into opportunities for developing health products based on local resources. For follow-up, it is recommended to develop product prototypes, compile a digital catalogue, and establish collaborations with relevant parties for program sustainability.